THU0181 Serum level of SYNDECAN-1 is associated with disease activity in patients with systemic lupus erythematosus. (23rd January 2014) - Kim, K.-J.; Kim, J.-Y.; Park, S.-J.; Baek, I.-W.; Yoon, C.-H.; Kim, W.-U.; Cho, C.-S.
Abstract : Background: Syndecan-1 (SDC1), a transmembrane heparan-sulfate glycoprotein, is predominantly expressed by plasma cells and is a receptor for a proliferation-inducing ligand (APRIL). SDC1 is readily shed and released into plasma under certain pathologic conditions and remains biologically active to affect cellular behaviour of plasma cells. Plasma cells are effector cells producing pathogenic autoantibodies in systemic lupus erythematosus (SLE). Objectives: To evaluate serum SDC1 concentration and to determine association between its levels and certain clinical manifestation in patients with SLE Methods: Serum samples from 127 patients with SLE and 24 normal healthy controls were assayed for SDC1 and APRIL by enzyme linked immunosorbent assay. Medical records were thoroughly reviewed for clinical features and serologic values. Disease activity was assessed using the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI). Results: Serum SDC1 levels were significantly elevated in patients with SLE compared to controls (61.2±6.5 versus 31.4±4.5 ng/ml, P <0.001). The level was correlated positively with anti-double stranded DNA (dsDNA) antibody titer and SLEDAI score (r =0.263, P =0.004, and g =0.231, P =0.012, respectively), but negatively with C3 and CH50 levels (r = -0.247, P =0.007 and r = -0.201, P =0.034, respectively). In particular, elevated levels of serum SDC1 were associated with the presence of active proteinuria (>0.5 gm/day) in SLE patients with lupus nephritis. Moreover, serum SDC1 levels had significant correlation with level of APRIL, which was known as surrogate marker of disease activity (r =0.507, P <0.001). Conclusions: Serum SDC1 levels are elevated and correlated with markers of disease activity in patients with SLE, suggesting that serum SDC1 could be used as a potential marker of disease activity in patients with SLE. Disclosure of Interest: None Declared